Conceptual Basis of Legal Monitoring Implementation in The System of Public Administration - Onyshchuk, Ihor; Onyshchuk, Svitlana; Rudenko, Olga (Journal of History Culture and Art Research, 2020)
In the study, the question of the theory and practice of legal monitoring is developed and the expediency of introducing legal monitoring into the system of public administration of Ukraine with the purpose of its perfection is substantiated. It is shown that the basis of monitoring is a system of indicators that characterize a concrete measure of a change in a particular phenomenon or process. The practice of applying the integral indicator of government administration to Governance Research Indicator Country Snapshot is presented. Moreover, examples of monitoring are provided for such indexes as government effectiveness; regulatory quality; rule of law. As a result of the study, a recommendation was made to assess the state of the state administration system, focused on the results of monitoring the effectiveness of legislation and its practice. The monitoring mechanisms are proposed for elimination of shortcomings in the legislation. The improvement of the legal system is an incentive for improving the legal and informational literacy of all categories of civil servants. Such a task can be solved by introducing new criteria into the system of attestation of specialists in public administration and court employees. This is necessary to add and refine the training programs for students in management and information specialties. Legal monitoring should be part of the administrative and legal reforms in Ukraine.